Changes in road-user behaviors following the installation of raised pedestrian crosswalks combined with preceding speed humps, on urban arterials. (April 2017) - Gitelman, Victoria; Carmel, Roby; Pesahov, Fany; Chen, Sarit
Highlights: Raised crosswalks combined with preceding speed humps were installed at non-signalized crosswalks on urban arterials. Raised crosswalk arrangements are found to correspond with decreased vehicle speeds. A greater share of drivers yield to pedestrians after raising pedestrian crosswalks. More pedestrians cross within the crosswalk boundaries. Raised crosswalks have a potential of improving pedestrian safety on busy urban roads. Abstract: In this study, raised pedestrian crosswalks were installed at non-signalized mid-block crosswalks situated on urban arterial and collector roads. A raised crosswalk is built by installing a trapezoidal speed hump on the crosswalk area, building a preceding circular speed hump, in each travel direction, and adding traffic signs. A controlled field-study was conducted at eight sites, sixteen pedestrian crosswalks, where road user behaviors were compared in the after versus before the treatment periods. Two settings of raised crosswalks were applied at the study sites: a 15 cm high trapezoidal hump combined with 8–10 cm high circular humps, and a 10–12 cm high trapezoidal hump combined with 6–8 cm high circular humps. Field observations included video-recordings and free-flow speed measurements. Following the installation of the raised crosswalks, at most sites, a substantial decrease was observed in vehicle travel speeds while approaching the crosswalks, which was maintained over-time. In addition, at some crosswalks, improvements were found in the rates of giving-way to pedestrians by the vehicles, vehicle-pedestrian conflicts and shares of pedestrians who cross within the crosswalk boundaries, while the changes in keeping safe crossing rules by pedestrians were mixed. Overall, the changes in road user behaviors following the installation of the raised crosswalks were positive and associated with safety improvement of pedestrian crossing conditions. Based on the study results, raised crosswalks with preceding speed humps can be promoted as a pedestrian safety-improving measure on busy urban roads.